Effect of Vitamin D Supplementation on Obesity‐Induced Insulin Resistance: A Double‐Blind, Randomized, Placebo‐Controlled Trial. Issue 4 (4th March 2018) - Cefalo, Chiara M.A.; Conte, Caterina; Sorice, Gian Pio; Moffa, Simona; Sun, Vinsin A.; Cinti, Francesca; Salomone, Enrica; Muscogiuri, Giovanna; Brocchi, Alex A.G.; Pontecorvi, Alfredo; Mezza, Teresa; Giaccari, Andrea
Abstract : Objective: The aim was to investigate whether vitamin D supplementation, combined with a hypocaloric diet, could have an independent effect on insulin sensitivity in subjects with both overweight and hypovitaminosis D. Changes from baseline in anthropometric parameters, body composition, glucose tolerance, and insulin secretion were considered as secondary outcomes. Methods: Eighteen volunteers who were nondiabetic and vitamin D deficient and had BMI > 25 kg/m 2 were randomized (1:1) in a double‐blind manner to a hypocaloric diet + either oral cholecalciferol at 25, 000 IU/wk or placebo for 3 months. Hyperinsulinemic‐euglycemic clamp to measure insulin sensitivity was performed at baseline and after intervention. Results: Body weight in both groups decreased significantly (−7.5% in the vitamin D group and −10% in the placebo group; P  < 0.05 for both), with no between‐group differences. Serum 25‐hydroxyvitamin D levels in the vitamin D group increased considerably (from 36.7 ± 13.2 nmol/L to 74.8 ± 18.7 nmol/L; P  < 0.001). Insulin sensitivity in the vitamin D group improved (from 4.6 ± 2.0 to 6.9 ± 3.3 mg·kg −1 ·min −1 ; P  < 0.001), whereas no changes were observed in the placebo group (from 4.9 ± 1.1 to 5.1 ± 0.3 mg·kg −1 ·min −1 ; P  = 0.84). Conclusions: Cholecalciferol supplementation, combined with a weight loss program, significantly improves insulin sensitivity in healthy subjects with obesity and might represent a personalized approach for insulin‐resistant subjects with obesity.